Implementasi Question Answering Berbasis Chatbot Telegram Pada Tafsir Al-Jalalain Menggunakan Langchain dan LLM - Febrian Rizki Adi Sutiyo; Harahap, Nazruddin Safaat; Surya Agustian; Reski Mai Candra (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Technological developments are very important for efficient, accurate and fast information retrieval. Tafsir Al-Jalalain is one of the famous Tafsir Al-Qur’an, and is used as a source of life guidance for muslims. To get information about tafsir, you can go through information media such as the internet or from experts in Tafsir Al-Qur’an. However, to get information it takes a lot of time to filter the information efficiently, accurately and quickly. This problem requires a system that is able to answer human questions accurately, effectively and quickly. In this research, it is hoped that the implementation of telegram Chatbot-based Question Answering using Langchain and LLM will be a solution for providing information on Tafsir Al-Jalalain that is accurate, effective and fast. The Question Answering system will carry out learning on the Tafsir Al-Jalalain data using a language model, namely the Large Language Model, so that it is expected to be able to provide accurate, effective and fast information. The evaluation results of the research by distributing questionnaires to students majoring in Al-Qur'an and Tafsir Science at UIN SUSKA Riau, as many as seven respondents, obtained a percentage of 84.29%